Developing AI Competencies in Future Educators: A Framework of Innovation Process - Hashim, Siti Noor Aneeis; Hj. Azid@Aziz, Nurulwahida; Abbas, Mohd Saleh; Maidin, Siti Sarah; Ab Ghani, Muhamad Amin; Nordin, Mohd Norazmi; Krishnan, Vijayaletchumy (SEEJPH, 2025)
As Artificial Intelligence (AI) continues to revolutionize the education sector, it is critical to prepare future educators with the necessary AI competencies to enhance their teaching practices and pedagogical strategies. This review explores the development of AI skills among teacher candidates, proposing a comprehensive framework for integrating AI into educator training programs. The paper evaluates the current state of AI competencies in teacher education, identifies gaps, and highlights best practices for fostering innovation in education through AI. Drawing on research from 2013 to 2024, the review examines key AI tools, their potential to transform teaching methods, and offers a forwardlooking perspective on building AI literacy in future educators. The framework presented aims to inform policy makers, curriculum developers, and educator preparation programs on effective strategies for AI competency development.